Rethinking the history of education: considerations for a new social history of education. - Westberg, Johannes; Primus, Franziska (Paedagogica Historica, 2023)
In the 2020s, there are both societal and academic reasons to reflect on the field of history of education. In this article, we focus on the issue of the social, which remains central to the field as we acknowledge that society shapes education and education shapes society. By exploring the social on theoretical, methodological and broader societal levels, we provide suggestions for how we can rethink the field of educational history in the future. In line with a postmodern emphasis on particularity and complexity, we do not present any simple or general answers. We do not promote a return to the social history accounts of the post-war era and its emphasis on social class, economic development and the state. Instead, we encourage efforts to rethink the terms social and society on the basis of both classic social history accounts and the lessons learned from new cultural history of education. What would a new social history of education look like in the twenty-first century, and how can we write updated histories on education and society today?